Perbuatan Melawan Hukum Oleh Penyelenggara Sistem Elektronik: Studi Pertanggungjawaban Perdata Google Play Store Terhadap Aplikasi Perjudian Terselubung - Nada Ulya Qinvi; Adhitya Rizky Prabowo (Legis Nexus: Jurnal Ilmu Hukum, 2026)
Based on Law Number 11 of 2008 concerning Electronic Information and Transactions, which was last amended by Law Number 1 of 2024, the Google Play Store is classified as a Private Electronic System Provider. As a global application distribution platform operating in Indonesian jurisdiction, Google is strictly bound by the positive laws applicable in the country. The purpose of this study is to examine the civil liability of Google Play Store as an Electronic System Provider for losses arising from the circulation of disguised gambling applications on its platform. Using a normative juridical approach with conceptual and statutory analysis methods, this study examines the gap between the regulatory obligations imposed by Indonesian cyber law and the reality on the ground that thousands of gambling applications disguised as online games have managed to escape the Google Play Store's content moderation system. The results of the study indicate that the five elements of Unlawful Acts as regulated in Article 1365 of the Indonesian Civil Code have been fulfilled, namely (1) unlawful acts in the form of negligence in moderation, (2) errors in the form of culpa, (3) actual losses suffered by users, (4) a proven causal relationship and (5) violation of legal obligations as an Electronic System Organizer based on the ITE Law and PP No. 71 of 2019. This study offers a comprehensive legal argument that Google Play Store can be held civilly liable as an Electronic System Organizer in Indonesia.